Protective Effects of Ultramicronized Palmitoylethanolamide (PEA-um) in Myocardial Ischaemia and Reperfusion Injury in VIVO. Issue 2 (August 2016) - Di Paola, Rosanna; Cordaro, Marika; Crupi, Rosalia; Siracusa, Rosalba; Campolo, Michela; Bruschetta, Giuseppe; Fusco, Roberta; Pugliatti, Pietro; Esposito, Emanuela; Cuzzocrea, Salvatore
Abstract : ABSTRACT: Myocardial infarction is the leading cause of death, occurs after prolonged ischemia of the coronary arteries. Restore blood flow is the first intervention help against heart attack. However, reperfusion of the arteries leads to ischemia/reperfusion injury (I/R). The fatty acid amide palmitoylethanolamide (PEA) is an endogenous compound widely present in living organisms, with analgesic and anti-inflammatory properties. The present study evaluated the effect of ultramicronized palmitoylethanolamide (PEA-um) treatment on the inflammatory process associated with myocardial I/R. Myocardial ischemia reperfusion injury was induced by occlusion of the left anterior descending coronary artery for 30 min followed by 2 h of reperfusion. PEA-um, was administered (10 mg/kg) 15 min after ischemia and 1 h after reperfusion. In this study, we demonstrated that PEA-um treatment reduces myocardial tissue injury, neutrophil infiltration, adhesion molecules (ICAM-1, P-selectin) expression, proinflammatory cytokines (TNF-α, IL-1β) production, nitrotyrosine and PAR formation, nuclear factor kB expression, and apoptosis (Fas-L, Bcl-2) activation. In addition to study whether the protective effect of PEA-um on myocardial ischemia reperfusion injury is also related to the activation of PPAR-α, in a separate set of experiments it has been performed myocardial I/R in PPARα mice. Genetic ablation of peroxisome proliferator activated receptor (PPAR)-α in PPAR-αKO mice exacerbated Myocardial ischemia reperfusion injury when compared with PPAR-αWT mice. PEA-um induced cardioprotection in PPAR-α wild-type mice, but the same effect cannot be observed in PPAR-αKO mice. Our results have clearly shown a modulation of the inflammatory process, associated with myocardial ischemia reperfusion injury, following administration of PEA-um.